Capital Controls and Exchange Rate Regimes: An Empirical Investigation - Helge Berger; Jan-Egbert Sturm; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2001)
It is often argued that deregulation of international transactions and its effects on the globalization of financial markets is behind the decline in the attractiveness of fixed exchange rate regimes. We argue that, instead, much of the recently observed decrease in the level of capital controls should be seen as endogenous to the exchange rate regime decision. We find that the durability of a peg (measured on the basis of the growth of international reserves), the political benefits of a commitment to a peg, domestic and foreign inflation (aversion), as well as business cycle volatility and synchronization are the main determinants of capital controls. The empirical analysis is based on data for 53 non-OECD countries covering the period 1980-94.
Keywords: 330; Monetary policy; exchange rates; capital controls